Body heat storage and physiological responses of periparturient Karan Fries and Sahiwal cows during summer and winter season - Vaidya, Mangesh M; Singh, Sohan Vir (Indian Journal of Animal Nutrition, 2019)
The experiment was conducted during summer and winter season on pregnant and lactating high and low producing Sahiwal and Karan Fries cows. Ten each of periparturient Karan Fries and Sahiwal cows were selected separately during summer and winter season from Livestock Research Centre of ICAR- National Dairy Research Institute Karnal (Haryana). Further, these animals were equally divided (five each) into high and low producing group during both the seasons on the basis of their earlier lactation milk yield. These animals were maintained on standard conditions of feeding and management followed at the institute farm. The physiological responses (RR, PR, Tre and Tskin) and climatic variables (Tdb, Twb, Tmax, Tmin,RH and THI) were recorded -45, -30, -15, 0, 15, 30, and 45 with respect to day of parturition and the heat storage of the animals were calculated. The physiological responses viz. rectal temperature, respiration rate, skin temperature, pulse rate and heat storage were significantly (P<0.05) higher during summer season compared to winter season.Â The magnitude of increase in physiological responses were higher (P<0.05) in Karan Fries high and low producing cows compared to both the groups of Sahiwal cows during both the seasons. The mean values of heat storage increased to 6.2 and 1.8% in high and low yielding Sahiwal cows during summer season and in high and low yielding Karan Fries the values of heat storage increased to 6.7 and 5.4% respectively on the day of calving from the pre calving values (45 day). During winter season the values of heat storage increased to 2.6 and 4.4% in high and low yielding Sahiwal cows and inÂ Â high and low yielding KF cows the values of heat storage increased to 6.1 and 6.04% respectively on the day of calving from the pre calving values (45 day). The values of physiological responses return back to normal after 15th day of postpartum in both the breeds of cattle during both the seasons. Based on the present study, it can be recommended that the animals must be provided care and management including feeding during peripartum period and extreme climatic conditions. The higher deviations in Heat storage and body responses in high yielders compared to low yielder cows, suggest extra care must be given to high yielder animals.